Ответы и объяснения

  • irakim
  • почетный грамотей
2013-05-10T10:21:40+00:00

3{x-8y-17=0

{3x-4y-23=0

3х-24у-51=0

3х-4у-23=0

-20у-28=0

-20у=0+28

-20у=28

у=-1,4

3х-4*(-1,4)-23=0

3х+5,6-23=0

3х-17,4=0

3х=17,4

х=5,8

 

 {15x+11y-47=0

3 {5x-y+17=0

15х+11у-47=0

15х-3у+51=0

14у-98=0

14у=98

у=7

15х+11*7-47=0

15х+77-47=0

15х+30=0

15х=-30

х=-2

 

 3{8x-9y-21=0,          

8 {3x-2y-12=0;

24х-27у-63=0

24х-16у-96=0

-11у+33=0

-11у=-33

у=3

24х-27*3-63=0

24х-81-63=0

24х-144=0

24х=144

х=6